Structure activity relationships of benzylproline-derived inhibitors of the glutamine transporter ASCT2. Issue 3 (1st February 2017) - Singh, Kurnvir; Tanui, Rose; Gameiro, Armanda; Eisenberg, Gilad; Colas, Claire; Schlessinger, Avner; Grewer, Christof
Graphical abstract: Abstract: The glutamine transporter ASCT2 has been identified as a promising target to inhibit rapid growth of cancer cells. However, ASCT2 pharmacology is not well established. In this report, we performed a systematic structure activity analysis of a series of substituted benzylproline derivatives. Substitutions on the phenyl ring resulted in compounds with characteristics of ASCT2 inhibitors. Apparent binding affinity increased with increasing hydrophobicity of the side chain. In contrast, interaction of the ASCT2 binding site with specific positions on the phenyl ring was not observed. The most potent compound inhibits the ASCT2 anion conductance with a K i of 3 μM, which is in the same range as that of more bulky and higher molecular weight inhibitors recently reported by others. The experimental results are consistent with computational analysis based on docking of the inhibitors against an ASCT2 homology model. The benzylproline scaffold provides a valuable tool for further improving binding potency of future ASCT2 inhibitors.